Non-kekulean benzenoid hydrocarbon: physico-chemical properties for benzenoid hydrocarbon using topological indices and mpolynomial - Anns Uzair; Aiman Ishtiaq; Misbah Rasheed (Computational Algorithms and Numerical Dimensions)
Topological indices are the numerical values that are connected to subatomic graphs in order to create the quantitative structure activity and structure attribute of a chemical compound and non-chemical graphs. The molecular structure of both chemical and non-chemical graphs is explained by topological indices. The goal of the current study is to determine M-polynomials, which will then be used to determine the degree-based topological indices of non-kekulean benzenoid hydrocarbons for n > 1. For the non-kekulean benzenoid hydrocarbon, we determine the first K Banhatti index, modified first K Banhatti index, inverse sum index, randic index, symmetric index, harmonic index, first K Banhatti index, and K hormonic Banhatti index.